Studies on mechanical properties of aluminum based hybrid metal matrix composites. (2020) - Suresh Babu, B.; Prathap, P.; Balaji, T.; Gowtham, D.; Sree Adi, S.D.; Divakar, R.; Ravichandran, Sanjeev
Abstract: Aluminum alloy provides the best alternative to steel with improved performance over the more common metals and alloys frequently used in automotive industries and aerospace segment. Hybrid Aluminum Alloys Metal Matrix Composites (HMMCs) are gaining specific attentions in automotive and aerospace applications based on its low density, high strength and its good structural rigidity. In this research work, an investigation is made to fabricate and compare the mechanical and metallurgical properties of Al 6063-Silicon Carbide with Al 6063-Silicon Carbide/Graphite hybrid metal matrix composite materials. The composites were manufactured by means of stir casting techniques in which quantity of reinforcement is in the range from 5% to 15% in steps of 5 wt.% per sample. The manufactured composites are characterized by mechanical properties, density and microstructural studies and evaluated as per ASTM standards. The optical microphotographs of the composites are uniform distribution of the hybrid particles in the composites with few clusters. The experimental densities were found to be lower than, compare to the theoretical densities in all the composites. The dispersed Silicon Carbide and Graphite in Al 6063 alloy contributed to improving the tensile strength (MPa) of the composites. From scanning electron microscope (SEM) analysis, the samples were found having uniform distribution of the hybrid reinforcement particles (SiC.and Graphite) in the matrix without any tunnel and voids effects.